Pengaturan Pemblokiran Konten Penyebaran Kampanye Hitam Melalui Media Sosial - Kadek Mery Herawati (Fakultas Hukum, Universitas Warmadewa, 2024)
Social media is regarded as the fifth pillar of democracy. The role of the mass media as the controller of governance and democracy is increasingly recognized and is now regarded as the fourth pillar of the democratic system. However, along with the opportunities that exist, the digital age also poses a serious challenge to democracy. This spread of disinformation can confuse people, empower voters and influence their choices. Another challenge is black campaign attacks of false information or hoaks, insults and slander aimed at political opponents to knock each other down, carried out through social media. Starting from the issue, the author tried to analyze and describe further about the blocking of the spread of black campaign content through social media. This research is conducted in a normative jurisprudence, that is, by looking at the problem through the legal principles contained in Indonesian law. In article 280 (1) letter c of the Election Act, which regulates the prohibition of campaigns in elections, the rules on black campaigns on social media are not comprehensively written and do not have a clear definition. According to Article 40 (2) of the Electronic Information and Transactions Act, the Government is obliged to prevent the dissemination and use of Electronic information and/ or electronic documents that have a prohibited load in accordance with the provisions of the regulations of the laws. However, this blockage can only be made against Electronic info and/or electronic documents which have illegal content, and does not include the termination of Internet network access as a whole. To offset the possibility of Internet abuse, the government has established a Internet Restriction Policy. By limiting the use of media, i.e. blocking and filtering websites or social media, surveillance, forced deletion of content, thorough blocking of social media on platforms and other communications information technologies.